Dysphagic disorder in a cohort of COVID-19 patients: Evaluation and evolution. (September 2021) - Ceruti, Samuele; Glotta, Andrea; Galli, Anna; Biggiogero, Maira; Bona, Giovanni; Mauri, Romano; Saporito, Andrea; Capdevila, Xavier
Abstract: Background: COVID-19 is a multisystem disease complicated by respiratory failure requiring sustanined mechanical ventilation (MV). Prolongued oro-tracheal intubation is associated to an increased risk of dysphagia and bronchial aspiration. Purpose of this study was to investigate swallowing disorders in critically ill COVID-19 patients. Material and methods: This was a retrospective study analysing a consecutive cohort of COVID-19 patients admitted to the Intensive Care Unit (ICU) of our hospital. Data concerning dysphagia were collected according to the Gugging Swallowing Screen (GUSS) and related to demographic characteristics, clinical data, ICU Length-Of-Stay (LOS) and MV parameters. Results: From March 2 to April 30, 2020, 31 consecutive critically ill COVID-19 patients admitted to ICU were evaluated by speech and language therapists (SLT). Twenty-five of them were on MV (61% through endotracheal tube and 19% through tracheostomy); median MV length was 11 days. Seventeen (54.8%) patients presented dysphagia; a correlation was found between first GUSS severity stratification and MV days (p < 0.001), ICU LOS (p < 0.001), age (p = 0.03) and tracheostomy (p = 0.042). No other correlations were found. At 16 days, 90% of patients had fully recovered; a significant improvement was registered especially during the first week (p < 0.001). Conclusion: Compared to non-COVID-19 patiens, a higher rate of dysphagia was reported in COVID-19 patients, with a more rapid and complete recovery. A systematic early SLT evaluation of COVID-19 patients on MV may thus be useful to prevent dysphagia-related complications. Highlights: In COVID-19 patients, dysphagia is a consequence of a prolonged MV and tracheostomy. Gugging Swallowing Screen (GUSS) is the test used for dysphagia degree evaluation. Speech and language therapist has a key role in recovery phase of COVID-19 patients. Rapid and complete recovery has been observed after speech therapist intervention.